METAPHOR IN ONANG-ONANG SONG - ISMAIL HARAHAP; Meisuri Meisuri; Sisila Fitriany Damanik (Universitas Negeri Medan, 2020)
This study was about the use of metaphor in the onang-onang song. The goals of the study were: to find out the types of metaphor used in onang-onang song, describe the realization of each type, and explain the reasons of onang-onang song represent in the particular value. The descriptive-qualitative method was used in the analysis of metaphor. The data of the study taken from six Onang-onang songs and have 67 utterances 11 lines have metaphor meaning. The results of the data analysis showed that there were three types of metaphor: conceptual (45.4%),and followed by ontological (36.3%), and orientational metaphor (18.1)%. The song were realized linguistically by identifying in each of the uterancess to get the implicit message in the song. The onang-onang songs were used in cultural values because all of the message in each of lyrics has a good meaning such as adviced, shared experience, and also kind of prayer to the new mariage life. So to make this study be strong, a tribal leader has an important role to translate of each lyrics.